2013
DOI: 10.3233/jad-121777
|View full text |Cite
|
Sign up to set email alerts
|

Aftins Increase Amyloid-β42, Lower Amyloid-β38, and Do Not Alter Amyloid-β40 Extracellular Production in vitro: Toward a Chemical Model of Alzheimer's Disease?

Abstract: Increased production of amyloid-β (Aβ)42 peptide, derived from the amyloid-β protein precursor, and its subsequent aggregation into oligomers and plaques constitutes a hallmark of Alzheimer’s disease (AD). We here report on a family of low molecular weight molecules, the Aftins (Amyloid-β Forty-Two Inducers), which, in cultured cells, dramatically affect the production of extracellular/secreted amyloid peptides. Aftins trigger β-secretase inhibitor and γ-secretase inhibitors (GSIs) sensitive, robust upregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…We examined whether impaired or attenuated activity of γ‐secretase may be influencing p3‐Alcβ levels by using the γ‐secretase modulator Aftin‐5, which increases Aβ42 generation and to lower generation of Aβ38 [39]. Other studies have shown an identical trend in p3‐Alcα generation: it increases p3‐Alcα38 generation while decreasing that of p3‐Alcα35 [24].…”
Section: Resultsmentioning
confidence: 99%
“…We examined whether impaired or attenuated activity of γ‐secretase may be influencing p3‐Alcβ levels by using the γ‐secretase modulator Aftin‐5, which increases Aβ42 generation and to lower generation of Aβ38 [39]. Other studies have shown an identical trend in p3‐Alcα generation: it increases p3‐Alcα38 generation while decreasing that of p3‐Alcα35 [24].…”
Section: Resultsmentioning
confidence: 99%
“…Decrease in γ-secretase activity can be a result of aging induced decrease in γ-secretase expression (Kern et al, 2006;Theuns et al, 2003). Different drug-candidates (Svedruzic et al, 2013;Mitani et al, 2012), and possibly environmental toxins (Hochard et al, 2013), can also decrease maximal activity of γ-secretase. Different pathogenic processes can be also simulated experimentally by decreasing expression of γ-secretase, or by increasing expression of APP substrate (German and Eisch, 2004;Marlow et al, 2003;Refolo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Colorimetric (Lavery, Brown, and Pope, 2001), such as enzyme-linked immunosorbent assay (ELISA; Hochard et al, 2013). Fluorescent, such as fluorescence resonance energy transfer, (FRET; Mere et al, 1999;Zhu, Fu, and Luo, 2012), dissociation-enhanced lanthanide fluorescent immunoassay (DEL-FIA; Newbatt et al, 2013), fluorescence polarization (Owicki, 2000), time resolved-FRET (TR-FRET), homogeneous time-resolved fluorescence (HTRF; Degorce et al, 2009;von Ahsen et al, 2006), fluorogenic substrates (Mitnaul et al, 2007), calcium flux (Luo et al, 2011), and membrane translocation (Vijayakumar, Ajay, and Bhat, 2010).…”
Section: Screening Assay Development and Validationmentioning
confidence: 99%